Current and future options for dental pulp therapy. Issue 1 (November 2019) - Morotomi, Takahiko; Washio, Ayako; Kitamura, Chiaki
Summary: Dental pulp is a connective tissue and has functions that include initiative, formative, protective, nutritive, and reparative activities. However, it has relatively low compliance, because it is enclosed in hard tissue. Its low compliance against damage, such as dental caries, results in the frequent removal of dental pulp during endodontic therapy. Loss of dental pulp frequently leads to fragility of the tooth, and eventually, a deterioration in the patient's quality of life. With the development of biomaterials such as bioceramics and advances in pulp biology such as the identification of dental pulp stem cells, novel ideas for the preservation of dental pulp, the regenerative therapy of dental pulp, and new biomaterials for direct pulp capping have now been proposed. Therapies for dental pulp are classified into three categories; direct pulp capping, vital pulp amputation, and treatment for non-vital teeth. In this review, we discuss current and future treatment options in these therapies.